An innovative hypochlorite-sensing scaffold and its imaging application in vivo. (July 2021) - Huang, Yongfei; Zhang, Yongbin; Huo, Fangjun; Yin, Caixia
Abstract: In recent years, coumarin fluorescent probes have been widely used in the detection of environmental pollutants, disease diagnosis and drug development due to their excellent optical properties, good water solubility and easy structure modification. Most coumarin fluorescent probes are modified at 3 and 7 positions mainly by introducing substituents, while at 4 and 8 positions are relatively less modified. Herein, compound 2 and 3 were prepared by introducing electron-donating group (EDG) and electron-withdrawing group (EWG) into the 4 position of 7-diethylamino-3-acetyl coumarin, respectively, and their properties were studied by theoretical calculation and spectral test. Then, we successfully prepared Probe 1 and Probe 2 by introducing pyrazoline ring at 7 position. Probe 2 exhibited high quantum yield and rapid response to ClO − in pure PBS. We speculated that it is a synergistic action of –OH and pyrazoline rings. In addition, Probe 2 could effectively detect ClO − in HeLa cells and zebrafish. Modification of substituents in different positions is a novel concept for the construction and optimization of fluorescent probes, which will provide a more effective tool for solving practical problems. Graphical abstract: Image 1 Highlights: The structure and properties of 7-diethylamino-3-acetyl coumarin were optimized based on pyrazoline ring. The probe showed high fluorescence quantum yield and fast response to ClO − in pure PBS. The probe with excellent performance shows good applications in HeLa cells and zebrafish.